The Academic Freedom among the Students at the Hashemite University - Al-Zyoud, Abd AlKhaleq Muhammad (Journal of Educational and Psychological Sciences, 2020)
This study aimed at exploring the level of academic freedom at the Hashemite University in Jordan from the perspective of the undergraduate students, and whether there are impacts of the students’ gender, academic level, or specialization. The sample consisted of (376) undergraduate students (111 male, 265 female), who are registered at the university for the first semester of the academic year 2019/2020, from all faculties of the Hashemite University. The results showed that 25.5% of participants perceived a high level of academic freedom, 57.2% of participants perceived a moderate level, and 17.3% of them perceived a low level. Significant differences were found due to academic level; academic freedom perceived level among senior students was higher than all other years (freshmen, sophomores and juniors), but no significant differences were found due to students’ gender, or specialization. In light of the study results, the researcher recommends a number of recommendations such as: raising the awareness about the academic freedom among the students, faculty members, and the staff the Jordanian universities, conducting survey studies that measure the level of academic freedom among the students at various Jordanian universities, Supporting the academic freedom of the students at the institutions of higher education through deliberate and planned initiatives.